2017
DOI: 10.4172/2168-9717.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Satisfaction Rate in Affordable Housing Case Study: Ardabil Mehr Housing in Ardabil Province of Iran

Abstract: Journal of Architectural Engineering Technology AbstractProviding appropriate housing for the people is one of the responsibilities of the governments such as Islamic republic of Iran government. In recent years the government decided to implement the mass housing for low-income households, that this project was called "Mehr housing". The aim of current research was evaluation the satisfaction rate of Mehr housing residents in Ardabil city, northwest of Iran. Heads of 120 household residents of Ardabil Mehr ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Overall, it is clear that residents at Al-Sharq are never satisfied with the current conditions or features in their residential areas. Therefore, the findings of this study support past research findings (Karimzadeh et al, 2015;Mohit and Al-Khanbashi, 2014;Azemati, Pourbagher and Rostami, 2017), which found that the demands of low and medium-income residents in non-gated residential areas have not been met and that residents are not satisfied with their affordable houses. However, the study findings contrast with those of Karimzadeh et al (2015), which concluded that there are no resident problems within the affordable housing in NGR.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, it is clear that residents at Al-Sharq are never satisfied with the current conditions or features in their residential areas. Therefore, the findings of this study support past research findings (Karimzadeh et al, 2015;Mohit and Al-Khanbashi, 2014;Azemati, Pourbagher and Rostami, 2017), which found that the demands of low and medium-income residents in non-gated residential areas have not been met and that residents are not satisfied with their affordable houses. However, the study findings contrast with those of Karimzadeh et al (2015), which concluded that there are no resident problems within the affordable housing in NGR.…”
Section: Discussionsupporting
confidence: 88%
“…In this case, various studies reported that residents of Mehr housing complexes dissatisfied with economic aspects (e.g. purchase cost and mortgage payments of the complex), poor access to land uses including shopping, educational, health, recreational centers and public transportation stations (Rezaei and Kamaizadeh, 2012;Pourdehimi, 2011;Shahriari et al, 2014;Azizi and Rahmani, 2014;Jahanshahloo and Daroudi, 2015;Noori and Asadpoor, 2016;Azemati et al, 2017;Zanganeh Shahraki et al, 2020). In contrast, the results of the study conducted by Daroudi et al (2015) illustrated that residents were relatively satisfied with adequate access to land uses and municipal service of Mehr housing complex in Hashtgerd (a small city in Alborz province located in the west of Tehran which is capital city of Iran).…”
Section: Residential Satisfaction In Northern Iranmentioning
confidence: 99%
“…purchase cost and mortgage payments of the complex), poor access to land uses including shopping, educational, health, recreational centers and public transportation stations (Rezaei and Kamaizadeh, 2012; Pourdehimi, 2011; Shahriari et al. , 2014; Azizi and Rahmani, 2014; Jahanshahloo and Daroudi, 2015; Noori and Asadpoor, 2016; Azemati et al. , 2017; Zanganeh Shahraki et al.…”
Section: Introductionmentioning
confidence: 99%
“…A group of researchers has investigated residential satisfaction at the scale of urban apartments to residential complexes (Zabihi, Habib, & Rahbarimanesh, 2011;Abbaszadeh, Gohari, & Askari Rabori, 2017). Another group has examined this concept at the neighborhood or urban scale (Dekker, de Vos, Musterd, & van Kempen, 2011;Azemati, Pourbagher, & Rostami, 2017). Moreover, another group has examined this concept on the scale of urban geography (Theodori, 2001).…”
Section: The Concept Of Residential Satisfactionmentioning
confidence: 99%